Neutrophil to Lymphocyte Ratio, Platelet to Lymphocyte Ratio, and Lymphocyte to Monocyte Ratio in Gastric Cancer Patients Compared with the Control Group and Its Association with Pathological Factors of the Disease - I Maleki; M Eslami-Jouybari; H Memari; A Hedayatizadeh-Omran; H Asgarian-Omran; R Alizadeh-Navaei (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2023)
Background and Objective: Considering the prevalence of gastrointestinal cancers in the region and the importance of helpful criteria in the diagnosis of the disease, the present study was conducted to compare the blood parameters neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR) and lymphocyte to monocyte ratio (LMR) in gastric cancer patients in Mazandaran province and its comparison with non-affected people. Methods: This cross-sectional study was conducted in 2019 and 2020 on 62 cancer patients referred to Imam Hospital in Sari in the case group and 124 non-patients from the community in the control group. Convenience sampling was used in the case group and random sampling was used in the control group from among the Tabari Cohort Population. The two groups were matched in terms of age and gender. The required data including age, gender, LMR, NLR and PLR for all subjects as well as pathological indices and chemotherapy status were recorded for the case group. Findings: The gender ratio in both groups was 69.4% males and 30.6% females. The mean age of the examined subjects in the group of cancer patients and the control group was 62.3±12.53 and 51.7±9.02 years, respectively (p=0.105). The mean NLR (2.14 vs. 1.62, p=0.000) and PLR (9.48 vs. 6.27, p=0.000) in the group with gastric cancer were significantly higher than the healthy control group, and the mean LMR (3.42±2.12 vs. 10.9±2.99, p=0.000) was significantly lower than the healthy control group. Conclusion: The results of high NLR and PLR and low LMR showed that these indices can be used in gastric cancer screening studies.